A new approach for ultrahigh-performance piezoresistive sensor based on wrinkled PPy film with electrospun PVA nanowires as spacer. (November 2017) - Luo, Cheng; Liu, Nishuang; Zhang, Hang; Liu, Weijie; Yue, Yang; Wang, Siliang; Rao, Jiangyu; Yang, Congxing; Su, Jun; Jiang, Xueliang; Gao, Yihua
Abstract: Pressure sensor with high sensitivity is desirable for it's vast application in fields like wearable electronics and human-machine interface. Here, we report a simple but rarely investigated approach to fabricate amazing high sensitivity pressure sensors by using PVA nanowires as spacer between active materials. On one hand, Polyvinyl Alcohol (PVA) nanowire (PVANW) serves as contact spacer between polypyrrole (PPy) film and PET/ITO sheet, where the electrical transportation between PPy film and PET/ITO sheet can be altered with different density of PVANW; on the other hand, the electroplating-obtained PPy film with intrinsic wrinkled and fluffy structure, shows various electrical conductivities under various external pressures. By virtue of these two traits, the PPy-PVANW-PET/ITO (PPPI) sensor distinguishes itself with superior performances of ultrahigh sensitivity (109.9 kPa −1, 0–0.17 kPa; 228.5 kPa −1, 0.5–2 kPa; 11.9 kPa −1, 5–9 kPa), low detection limit (2.97 Pa) and good stability (10, 000 loading-unloading cycles). The excellent advantages of the sensor make it a promising candidate in today's pressure sensor industry, and the fabrication procedure of PPPI sensor also provides a simple method to improve the performance of pressure sensors. Graphical abstract: Highlights: PVA nanowires are assembled into the sensor as spacer to control the conductive path. The sensor shows a high sensitivity of 228.5 kPa −1 and a detection limit of 2.97 Pa. The easy approach provides a new way towards high performance pressure sensor.